Digitalization of the Educational Process as an Effective Tool for Improving Its Quality - Mutovkina, Nataliya (Innovations in Pedagogy and Technology, 2025)
The article discusses the results of electronic information and the educational environment at Tver State Technical University over the past few years in connection with the general trend of digital transformation of the educational process in Russian universities. The electronic information and educational environment is a system that permeates all structural divisions of the University and provides significant support for their interaction. The article shows her structure and the specifics of its use, and defines the tasks and capabilities of all user categories. The research novelty is a systematic approach to assessing the quality of an educational system based on digital technologies. The digitalization of the educational process, namely the development of an electronic information and educational environment, has a positive effect on the performance of all its participants. The electronic information and educational environment contribute to the evolution of students’ analytical and communicative competencies and early adaptation to the educational process. The advantages of conducting training sessions in computer classrooms and the difficulties associated with their organization are the other. Access to electronic training courses from computer-equipped classrooms permits students to receive up-to-date information on their subjects, better understand the essence of academic assignments, and interact with teachers and fellow students. The article contains recommendations on the use of computers and information and communication technologies in education. We discuss the possibilities of further development of the electronic information and educational environment to improve the effectiveness of education.